2007
DOI: 10.1021/ol701590b
|View full text |Cite
|
Sign up to set email alerts
|

First Total Synthesis of Vialinin A, a Novel and Extremely Potent Inhibitor of TNF-α Production

Abstract: Vialinin A, a powerful inhibitor (IC50 90 pM) of TNF-alpha production, was synthesized from sesamol in 11 steps with 28% overall yield. The key reactions include a double Suzuki coupling of electron-rich aryl triflate with phenylboronic acid and an oxidative deprotection of bis-MOM ether. In addition, the related synthetic studies also suggest the necessity for structural revision of ganbajunin C, a positional isomer of vialinin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Starting from sesamol 6 , we optimized the synthetic route to the methoxymethyl (MOM)‐protected catechol 9 used before for acyl‐DBD dyes, and managed to introduce the desired ethyl esters ( 10 a ) 13. After cleavage, catechol 11 a was cyclized with benzyl‐protected propiolic acid by using 4‐dimethylaminopyridine (DMAP) 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from sesamol 6 , we optimized the synthetic route to the methoxymethyl (MOM)‐protected catechol 9 used before for acyl‐DBD dyes, and managed to introduce the desired ethyl esters ( 10 a ) 13. After cleavage, catechol 11 a was cyclized with benzyl‐protected propiolic acid by using 4‐dimethylaminopyridine (DMAP) 9.…”
Section: Resultsmentioning
confidence: 99%
“…The 17-and 32-labelled Gly 13 Cys variant displays fluorescence lifetime changes ( Figure 12) that suggest that the envi-ronment changes from apolar to polar as the lobes of MBP close, because the fluorescence lifetime of 32 decreases by 1.3 ns and that of 17 increases by about 3 ns after the addition of maltose. The reciprocal behavior of the two male-A C H T U N G T R E N N U N G imide labels provides internal confirmation of the consistency of these data, which is consistent with the shift of the emission maxima to longer wavelengths by 4 nm with 32 in the closed conformation, whereas those of 17 remain constant.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Recently, Takahashi et al have reported the total synthesis of a similar compound vialinin A, by a similar cross-coupling strategy. 4 O O…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of quinone coupling partner 20c was based primarily on the Suzuki coupling strategy charted recently in syntheses of the terphenyl natural products terprenin48 and vialinin A49 (Scheme 6). The tetrabenzyl ether 64 was brominated,50 then coupled48 with boronic acid 66 to form the biaryl 67 .…”
Section: Results and Discusssionmentioning
confidence: 99%